Modulation of gut microbiota, up-regulation of ZO-1, and promotion of metabolism as therapeutic mechanisms of indole-3-carbinol against obesity in mice - Mao, XuWen; Paerhati, Guliruoyi; Wu, Yuche; Cheng, Lu Feng (Frontiers in Pharmacology, 2025)
BackgroundIndole-3-carbinol (I3C) is a compound derived from Cruciferous vegetables. We aim to ascertain whether I3C mediates the relations between mouse gut microbiota, intestinal barrier function, and metabolism to treat obesity in mice.MethodsThe experimental analyses focused on the changes in lipid distribution, inflammatory cytokines, glucose tolerance, gut microbiota composition, and serum metabolomics of 60 C57BL/6N mice.ResultsThe experimental results demonstrated that I3C reduced body weight, hepatic steatosis, and systemic inflammation and improved insulin resistance in mice on a high-fat diet (HFD). Furthermore, I3C remarkably enhanced the enrichment of probiotics Akkermansia and Ligilactobacillus as well as SCFA-producing bacteria (Eubacterium, Lactococcus, and Coprococcus), while reducing the abundance of Eisenbergiella and Rikenellaceae_RC9_gut_group. Also, I3C notably up-regulated the levels of Claudin4, Occludin, and ZO-1 proteins and modulated the metabolism of argininosuccinic acid and galactose.ConclusionThe aforementioned findings suggest that I3C exerts a significant anti-obesity effect in mice by regulating abnormal gut microbiome, enhancing intestinal barrier function, and improving metabolic disorders.